Boosting Li-CO2 battery performances by creating holey structure on CNT cathodes. (10th June 2022) - Xie, Huamei; Zhang, Biao; Hu, Chuangang; Xiao, Ning; Liu, Dong
Abstrac: Li-CO2 batteries have attracted more and more attention because of their high theoretical energy density and promising CO2 capture capacity. However, irreversible formation of Li2 CO3 during discharging causes a high overpotential, short cycling life, and poor rate capability. To enable Li-CO2 batteries stable and rechargeable operation, the development of high-efficiency catalysts for CO2 reduction and Li2 CO3 decomposition is highly desired. Herein, holey carbon nanotubes (CNTs) are developed as the cathode catalysts for the rechargeable Li-CO2 batteries. Benefiting from abundant defects for enhancing CO2 reduction/evolution reactions and holey structures for storing more discharge products, and combining advantage of high conductivity of CNTs for rapid electron transport, the as-prepared Li-CO2 batteries with holey CNTs exhibited a low overpotential of 1.18 V at 50 mA g −1 . More importantly, the batteries delivered an ultrahigh discharge capacity of 17, 500 mA h g −1 and long-time stability over 1500 h at 100 mA g −1 . This study unlocks new avenues to develop high-efficiency cathode catalysts for high-performance metal-CO2 batteries and beyond. Graphical abstract: Image, graphical abstract